Silk and its composites for humidity and gas sensing applications - Jain, Shubhanth; Vedavyas, V.; Prajwal, R. V.; Shaji, Malavika; Nath, Vishnu G; Angappane, S.; Achutharao, Govindaraj (Frontiers in Chemistry, 2023)
Silk fibroin (SF) is a natural protein largely used in the textile industry with applications in bio-medicine, catalysis as well as in sensing materials. SF is a fiber material which is bio-compatible, biodegradable, and possesses high tensile strength. The incorporation of nanosized particles into SF allows the development of a variety of composites with tailored properties and functions. Silk and its composites are being explored for a wide range of sensing applications like strain, proximity, humidity, glucose, pH and hazardous/toxic gases. Most studies aim at improving the mechanical strength of SF by preparing hybrids with metal-based nanoparticles, polymers and 2D materials. Studies have been conducted by introducing semiconducting metal oxides into SF to tailor its properties like conductivity for use as a gas sensing material, where SF acts as a conductive path as well as a substrate for the incorporated nanoparticles. We have reviewed gas and humidity sensing properties of silk, silk with 0D (i.e., metal oxide), 2D (e.g., graphene, MXenes) composites. The nanostructured metal oxides are generally used in sensing applications, which use its semiconducting properties to show variation in the measured properties (e.g., resistivity, impedance) due to analyte gas adsorption on its surface. For example, vanadium oxides (i.e., V2O5) have been shown as candidates for sensing nitrogen containing gases and doped vanadium oxides for sensing CO gas. In this review article we provide latest and important results in the gas and humidity sensing of SF and its composites.